Membrane Oxygenator for Extracorporeal Blood Oxygenation - Enny Ratnaningsih; Putu T.P. Aryanti; Nurul F. Himma; Anita K. Wardani; K. Khoiruddin; Grandprix T.M. Kadja; Nicholaus Prasetya; I Gede Wenten (Journal of Engineering and Technological Sciences, 2021)
Extracorporeal blood oxygenation has become an alternative to supply O2 and remove CO2 from the bloodstream, especially when mechanical ventilation provides insufficient oxygenation. The use of a membrane oxygenator offers the advantage of lower airway pressure than a mechanical ventilator to deliver oxygen to the patient’s blood. However, research and development are still needed to find appropriate membrane materials, module configuration, and to optimize hydrodynamic conditions for achieving high efficient gas transfer and excellent biocompatibility of the membrane oxygenator. This review aims to provide a comprehensive description of the basic principle of the membrane oxygenator and its development. It also discusses the role and challenges in the use of membrane oxygenators for extracorporeal oxygenation on respiratory and cardiac failure patients.